Gray hair influences perceived age and social perceptions - Nutt, Kallye M.; Thorstenson, Christopher A.; Yorzinski, Jessica L. (Frontiers in Psychology, 2025)
Physical traits can influence how people are perceived and evaluated by others, often reflecting underlying qualities considered important for social interaction. Gray hair color is one such trait that can potentially alter social perceptions related to aging, but has rarely been investigated independently from other correlated physical characteristics. The aim of the current work is to investigate how gray hair independently influences important social evaluations including perceived age, attractiveness, social status, aggressiveness, and trustworthiness. Participants (N = 120) were presented with images of male and female faces that exhibited non-gray hair (brown, blonde or red), and versions of the same faces manipulated to have gray hair, and were asked to rate these faces according to those social evaluations. Linear mixed-effects models indicated that faces with gray hair were perceived as older and less attractive. Men (but not women) also perceived faces with gray hair as less trustworthy. Results showed that gray hair did not impact assessments of social status or aggression. These results suggest that gray hair is independently used as an indicator of some important social evaluations (age, attractiveness, and trustworthiness), while others (social status and aggression) may be better informed by other characteristics.